A predator-prey model of rice plant, sparrow, rat, and snake - Swastika, Putu Veri; Pahlevi, Ilyasa; Ramdhani, Novrizal; Ole, Yesaya Putra Dappa; Fakhruddin, Muhammad (Universitas Islam Negeri Raden Intan Lampung, 2023)
Rice is one of the most widely consumed food sources in Indonesia. The success of the rice harvest can be influenced by several factors, one of which is plant pests. This can threaten national food security. Predator-prey mathematical model can be constructed to explain the relationship between rice plants with plant pests. The predator prey model consist of ODE system describing 2 predators level one (rats and sparrows), 1 predator level two (snake) and prey (rice plants). In this model, nine equilibrium points are obtained with analysis of the behavior of the model at each of its equilibrium points. We successfully simulated the model using hypothetical parameters and the results are agrees with the analysis behavior. Several factors will make plant pest populations decrease even lost from the population is the natural death and interaction of rice with plant pests